PENGARUH TERAPI MEMBACA AL-QUR’AN UNTUK MENINGKATKAN KETENANGAN JIWA SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DI SMP N 40 PEKANBARU - Ainun, Nur; Umari, Tri; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of Al-Qur'an reading therapy on increasing the peace of mind of students at SMP N 40 Pekanbaru. This type of research is quantitative research with experimental methods using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study was the scale of measuring students' mental calm consisting of 58 items before validation, and after validation obtained 51 items with a valid validity of 0.423 and a reliability of 0.956.The subjects of this study were 8 students who were identified as having moderate levels of mental calm for students. The data analysis technique used is non-parametric statistical techniques using the Rank Spearman test. The results of the study proved the research hypothesis was accepted. From the Spearman Rank test results obtained r = 0.747 while the correlation coefficient r2 is 0.558. Thus there is an effect as big as 55.8% of Al-Qur'an reading therapy on the peace of mind of students. From the Wilcoxon test results it was found that the hypothesis was accepted, meaning that there was a difference in the students' mental calm before and after being given Al-Qur'an reading therapy.Key Words: Read the Qur'an, Peace of Mind, Group Guidance Service